On Voice in Poetry - Smith, David Nowell. author. aut Link
VIII, 202 p.
Keywords: What do we mean by 'voice' in poetry? In this work, David Nowell Smith teases out the diverse meanings of 'voice', from a poem's soundworld to the rhetorical gestures through which poems speak to us, in order to embark on a philosophical exploration of the concept of voice itself.